(untitled) (Cardiovascular Journal, 2023)
Background: Besides conventional risk factors, a novel risk factor hypovitaminosis D may play unique role in the development of coronary artery disease. Evidences suggest that people with low serum vitamin D level is associated with risk of acute MI even after adjusting for the known risk factors. This study was conducted to find out the association between serum vitamin D Level and angiographic severity of coronary artery disease in patients of acute myocardial infarction. Methods: One hundred and four patients of acute myocardial infarction undergoing coronary angiography in DMCH during May 2017 to April 2018 were the study population. The population were divided into 2 groups based on their serum vitamin D level; normal vitamin D (>30 ng/ml) and low vitamin D (≤30 ng/ml). Low vitamin D level again divided into 3 groups; insufficient (vitamin D 21 to 30 ng/ml), deficient (Vitamin D 10-20 ng/ml) and severely deficient having vitamin D <10 ng/ml. Coronary angiogram was done during index hospitalization. The severity of the coronary artery disease was assessed by vessel score and Gensini score.After calculation of Gensini score, 36 points was chosen as an appropriate cut-off value and patients were divided into two groups; those with a Gensini score ≤36 points was considered as having absent or mild coronary artery disease and those with a Gensini score >36 points was considered as having moderate to severe coronary artery disease. Association between serum vitamin D Level and angiographic severity of CAD was looked for. Results: Seventy seven (74.0%) of study population had vitamin D level ≤ 30 ng/ml, while 27(26.0%) patients had normal level. There was no significant association between common cardiovascular risk factors with vitamin D level. Double or triple-vessel CAD were more frequent in those with vitamin D levels ≤30 ng/ml as compared to those with normal vitamin D levels (>30 ng/ml) (P<0.05). Majority (48.1%) of patients had double vessel disease (DVD). Among them 4(8%) patients had normal serum vitamin D levels (>30 ng/ml) and 46 (92%) patients had low vitamin D (≤30 ng/ml). Mean Gensini score was found 20.8±5.1 in normal vitamin D (>30 ng/ml) and 48.3±13.3 in low vitamin D (≤30 ng/ml) (p<0.05). Moderate to severe CAD (Gensini score >36) was found in 54.1% of patients with vitamin D insufficiency (21-30 ng/dl) and 83.3% of patients with vitamin D deficiency (10-20 ng/dl) (p<0.05). Moderate negative correlation (r= -0.641; p=0.001) was found between Gensini score and serum vitamin D level of patients with acute myocardial infarction. Conclusion: Low serum vitamin D level is associated with increasing severity of coronary artery disease, docsumented angiographically among patients of acute myocardial infarction. Low serum vitamin D levels may be an emerging, independent, and potentially modiﬁable cardiovascular risk factor. Cardiovasc j 2023; 15(2): 124-131